An Investigation of Stimulus Pairing and Listener Training to Establish Emergent Intraverbals in Children with Autism - Vallinger-Brown, Mary (Anal Verbal Behav, 2014)
We examined two methods to facilitate the emergence of untaught intraverbal responses to children with autism. Listener behavior training (LT) involved reinforcement of a selection-based response following presentation of an array of pictures on an iPad® and an auditory instruction describing a characteristic of the picture. Stimulus pairing (SP) involved presentation of one picture in isolation on the iPad® and an auditory instruction describing a characteristic of the picture. Participants were not required to emit an overt vocal response during SP. Results indicate both procedures were effective at producing some untaught intraverbal responses, but a transfer of stimulus control procedure was required for two of the three participants to meet mastery criterion. Results are discussed in terms of necessary prerequisite skills for each procedure, and the requirement of an overt or echoic response to help facilitate the emergence of intraverbals.